Variability management in safety‐critical systems design and dependability analysis. Issue 8 (12th August 2019) - de Oliveira, André Luiz; Braga, Rosana; Masiero, Paulo; Parker, David; Papadopoulos, Yiannis; Habli, Ibrahim; Kelly, Tim
Abstract: Safety‐critical systems are of paramount importance for many application domains, where safety properties are a key driver to engineer critical aspects and avoid system failures. For the benefits of large‐scale reuse, software product lines (SPL) have been adopted in critical systems industry. However, the integration of safety analysis in the SPL development process is nontrivial. Also, the different usage contexts of safety‐critical systems complicates component fault modeling tasks and the identification of potential hazards. In this light, better methods become necessary to estimate the impact of dependability properties during Hazard Analysis and Risk Assessment. Existing methods incorporating the analysis of safety properties in SPL are limited as they do not include hazard analysis and component fault modeling. In this paper, we present the novel DEPendable Software Product Line Engineering (DEPendable‐SPLE) approach, which extends traditional SPL processes to support the reuse of safety assets. We also present a detailed analysis of the impact of product and context features on the SPL design, safety analysis, and safety requirements. We applied DEPendable‐SPLE to a realistic case study from the aerospace domain to illustrate how to model and reuse safety properties. DEPendable‐SPLE reduced the effort of safety analysis for certifying system variants. Abstract : Extending traditional software product line processes with the support for variability management on dependability analysis enables the systematic reuse of both design and dependability information, and generation of dependability assets. It contributes to reduce the effort and costs of achieving certification of safety‐critical systems. Understanding the impact of variation in product and usage context features on the system design and dependability analysis may contribute to increase the accuracy of the reused dependability assets.